1976
DOI: 10.1007/bf01541869
|View full text |Cite
|
Sign up to set email alerts
|

Orgasmic frequency and plasma testosterone levels in normal human males

Abstract: Twenty males participated in a 2-month study examining the relationship between 8 a.m. plasma testosterone levels and orgasmic frequency. Within subjects, higher levels of testosterone are associated with periods of sexual activity. Over subjects, however, the direction of the relationship is reversed. Mean testosterone levels were higher for sexually less active individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 15 publications
5
36
0
Order By: Relevance
“…It is well-recognized that married individuals tend to have more frequent sexual behavior than unmarried individuals, even if the extent of that difference varies by country and other contextual factors. 31 Our finding (of higher testosterone levels in less sexually active men) was in agreement with earlier findings, which reported that the mean testosterone levels were higher for less sexually active individuals 32 . However, we did not obtain evidence of the living circumstances of the single men, whether they lived alone on their own, or lived at home with their parents, a fact that could contextualize the single men's' higher testosterone levels.…”
Section: Discussionsupporting
confidence: 93%
“…It is well-recognized that married individuals tend to have more frequent sexual behavior than unmarried individuals, even if the extent of that difference varies by country and other contextual factors. 31 Our finding (of higher testosterone levels in less sexually active men) was in agreement with earlier findings, which reported that the mean testosterone levels were higher for less sexually active individuals 32 . However, we did not obtain evidence of the living circumstances of the single men, whether they lived alone on their own, or lived at home with their parents, a fact that could contextualize the single men's' higher testosterone levels.…”
Section: Discussionsupporting
confidence: 93%
“…We are dubious and tentatively accept at face value the usual finding that level of circulating T explains little --at most modest --variation in sexual behavior, as long as hormones are within the normal range Tsitouras et al 1982;Davidson et al 1983;Yesavage et al 1985;Sadowsky et al 1993). Also, we know that causation can work in the opposite direction as when men's T rises after viewing erotic material (Hellhammer et al 1985) or after coitus (Kraemer et al 1976). The administration of exogenous T to 31 normal men in stable heterosexual relationships, nearly doubling circulating T for up to eight weeks, had no more effect than a placebo on overt sexual behavior, but it did increase some sexual attitudes (Anderson et al 1992).…”
Section: Testosterone Work Differently Perinatally At Puberty and mentioning
confidence: 99%
“…Aakvaag, Bentdal, Quigstad, Walstead, Ronningen & Fonnum, 1978 ;Matsumoto, Takeyasu, Mizutani, Hamanaka & Ouzumi, 1970;Rose, 1969;Rose, Bourne, Poe, Mougey, Collins & Mason, 1969;Ursin, Baade & Levine, 1978; see also Christiansen, Knussmann & Couwenbergs, 1985). Sexual stimulation (Fox, Ismail, Love, Kirkham & Loraine, 1972 ;Knussmann, Christiansen & Couwenbergs, 1986 ;Kraemer, Becker, Brodie, Doering, Moos & Hamburg, 1976) and exercise (Sutton, Coleman, Casey & Lazarus, 1973;Vogel, Books, Ketchum, Zauner & Murray, 1985) can increase testosterone levels. Studies of testosterone levels during alcohol intoxication have produced conflicting findings, some showing a suppressive effect (e.g.…”
Section: Limitations Of Correlational Evidencementioning
confidence: 99%